Meta-analysis on antiamebic drugs for the treatment of amebic colitis - Gonzales, Ma. Liza Antoinette M.
Background: Infection with Entamoeba histolytica occurs worldwide and amebic colitis is the most common manifestation of invasive disease. Adequate therapy for amebic colitis is necessary to reduce severity of illness, prevent development of complicated disease and extraintestinal spread, and decrease transmission. Objectives: To evaluate the effectiveness and safety of antiamebic drugs for treating individuals with amebic colitis. Search Strategy: The following databases were searched: Cochrane Infectious Disease Group Specialized Register, Cochrane Central Register of Controlled Trials (CENTRAL) published in The Cochrane Library, MEDLINE, EMBASE and LILACS. The meta Register of Controlled Trials )mRCT) was also searched using 'amoebic' and 'amoeba' as search terms. For unpublished or ongoing trials, conference proceedings were searched and individual researches working in the field, organizations, and pharmaceutical companies were contacted. The reference lists and bibliographies of all studies identified by the above methods. Selection criteria: Randomized controlled trials of antiamebic drugs given alone or in combination, compared with placebo or to another antiamebic drug. Data collection & analysis: Two authors assessed methodological quality of the studies and outcome data independently. Clinical and parasitological failure rates, relapse and adverse events were calculated as relative risks with 95% confidence intervals. Separate analyses were performed for clinical and parasitological outcomes reported 1 to 14 days amd 15 to 60 days after end of treatment. When there was more than 1 trial comparing similar interventions and comparison groups, separate meta-analyses were prepared for each comparison. Sub group analysis of clinical type of amebic colitis (amebic dysentery and nondysenteric amebic colitis) and age groups (adults, 15 years old and greater and children, less than 15 years old) were included. Summary and individual trial relative risks were reported using random effects model. Statistical heterogeneity among the same interventions were determined by looking at the forest piot and by performing chi-squared test for heterogeniety using a p value of 0.10 to determine statistical significance. The I2 test were also used to quantify inconsistency across trials and a value greater than 50% was considered as substantial heterogeneity. Possible sources of heterogeneity were explored when present. Sensitivity analysis using trial quality was used to assess robustness of the meta-analysis among the same interventions. Publication bias was determined by looking for asymmetry in a funnel plot. Main results: Thirty-seven randomized controlled trials studying 27 different antiamoebic drugs were included in the review. Stool microscopy was the only method used to identify the presence of E. histolytica cysts or trophozoites. Overall, the trials had moderate to high risk for bias. Three trials compared antiamebic drugs with placebo and evaluated 93 participants for clinical failure and 530 for parasitological failure 1 to 14 dats after end of treamtnet. Antiamebic drugs resulted in significant reduction in clinical failure (RR 0.36, 95% CI 0-23-0.56) and parasitological failure (RR 0.37, 95% CI 0.29-0.47), with no significant difference in adverse events. Twenty trials compared any antiamebic drug given alone or in combination with metronidazole and included 1,999 participants evaluated for clinical outcome and 1,827 for parasitological outcome. Compared with metronidazole alone, other antiamebic drugs resulted in significant reduction in clinical failure 1 to 14 days after end of treatment (RR 0.24, 95% CI 0.12-0.48) and 15 to 60 days after end of treatment (RR 0.44, 95% CI 0.25-0.77) with no significant difference in adverse events. There was no significant difference in parasitological failure in those given other antiamebic drugs compared to metronidazole. Of the antiamebic drugs compared with metronidazole, 10 trials studied tinidazole and included 702 evaluated for clinical outcome and 732 for parasitological outcome. Tinidazole resulted in significant reduction in clinical failure 15 to 60 days after end of treatment (RR 0.28, 95% CI 0.15-0.51) and was associated with less adverse events (RR 0.65, 95% CI 0.46-0.92). There was no significant difference in reduction of parasitological failure in those on tinidazole compared to metronidazole. Three trials compared metronidazole alone with combination therapy and evaluated 1,025 participants for clinical failure and 720 for parasitological failure 1 to 14 days after end of treatment. Metronidazole alone resulted in a tendency for increase in clinical failure (RR 3.05, 95% CI 1.02-9.15) and a significant increase in parasitological failure (RR 2.75, 95% CI 1.17-6.48). There is insufficient number of trials or participants to detect any difference in clinical and parasitological failure rates in the other antiamebic drugs. There is insufficienct data to detect any difference in relapse in those given antiamebic drugs. Reviewers' conclusions: Antiamebic drugs were more effective in reducing clinical and parasitological failure compared to placebo. Among the antiamebic drugs compared with metronidazole, tinidazole may be more effective in reducing clinical failure and may be comparable to metronidazole in reducing parasitological failure with less associated adverse events. Combination drug therapy may be more effective in reducing clinical and parasitological failure rates compared to metronidazole alone. There is insufficient evidence to recommend which among the antiamebic drugs to use alone or in combination. The overall quality of evidence was low to very low in the trials included in the review and further and better quality trials are needed. Diagnostic tests that are able to differentiate E. histolytica from other nonpathogenic strains should be used to confirm the diagnosis of amebic colitis.
xxiii, 403 leaves
Keywords: Antiamebic drugs; Amebic colitis